2001
DOI: 10.1021/om001028m
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Oxidations:  Inhibition of a Pd−H Elimination by Coordination of a Remote Carbon−Carbon Double Bond

Abstract: Under oxidative conditions that use an anionic palladium salt as catalyst, cis-endo-2,3-bis(hydroxymethyl)bicyclo[2.2.1]hept-5-ene affords the corresponding exo-lactol, while cis-endo-2,3-bis(hydroxymethyl)bicyclo[2.2.1]heptane provides the expected lactone. Mechanistic considerations explain how the presence of the CC bond blocks the oxidation at the lactol in the first case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…The above results clearly demonstrated that the lack of formation of 24 from 22 under Pd-conditions was attributable to the C=C bond. Analysis of both the plausible intermediates of the process and literature [39][40][41] to the carbonyl unit [42,43], is prevented in 8 E. That favors alkoxyde exchange with diol 22 to afford 8 F. The latter is in equilibrium with 8 B which evolves towards 23, that is, the more stable isomer [44][45][46]. The apparent absence of 23 evolution under the PdCl 2 /Adogen 464/DCE conditions would be a "no reaction" reaction [47,48], which involves 8 B, 8 C, 8 D, 8 E, alcoholysis and equilibration regenerating the starting substrate.…”
Section: (14)mentioning
confidence: 99%
See 1 more Smart Citation
“…The above results clearly demonstrated that the lack of formation of 24 from 22 under Pd-conditions was attributable to the C=C bond. Analysis of both the plausible intermediates of the process and literature [39][40][41] to the carbonyl unit [42,43], is prevented in 8 E. That favors alkoxyde exchange with diol 22 to afford 8 F. The latter is in equilibrium with 8 B which evolves towards 23, that is, the more stable isomer [44][45][46]. The apparent absence of 23 evolution under the PdCl 2 /Adogen 464/DCE conditions would be a "no reaction" reaction [47,48], which involves 8 B, 8 C, 8 D, 8 E, alcoholysis and equilibration regenerating the starting substrate.…”
Section: (14)mentioning
confidence: 99%
“…process and literature [39][40][41] led to the proposal of Scheme 8. The reaction of hydroxyaldehyde 8 B obtained via 8 A leads to alkoxypalladium intermediate 8 C. Subsequent intramolecular reaction occurs through the stereoselective approach of the alkoxypalladium moiety to one face of the aldehyde to afford 8 D. In contrast to the intermediate obtained from 25, 8 D undergoes a ligand exchange leading to palladacycle 8 E. The syn relationship between O-Pd and C-H bonds, which would allow a β-H elimination leading to the carbonyl unit [42,43], is prevented in 8 E. That favors alkoxyde exchange with diol 22 to afford 8 F. The latter is in equilibrium with 8 B which evolves towards 23, that is, the more stable isomer [44][45][46].…”
Section: (14)mentioning
confidence: 99%
“…Influence of the Pd environment on the reaction pathways of 1-indanol. 5 See discussion and references in [24].…”
Section: Figurementioning
confidence: 99%
“…Golding's team briefly reported that treatment of 22 with catalytic Pd(PPh 3 ) 4 in PhH at room temperature gave (E)-1,4-diacetoxy-2-butene (23) *55+. At 70-72°C in THF, we obtained a mixture of 23 and 1,2-diacetoxy-3-butene (24). The two compounds were also produced in DMF.…”
Section: η 1 -Versus η 3 -Allylpalladiummentioning
confidence: 99%
“…[10] With carbon tetrachloride, secondary aliphatic and benzylic alcohols were efficiently oxidized but allylic alcohols with a double bond in a terminal position did not give the corresponding a,b-unsaturated ketones because CCl 4 readily underwent Pd-catalyzed addition to the double bond. With 1,2-dichloroethane [11] as a co-oxidant, problems were encountered in the oxidation of primary alcohols, which gave mixtures of aldehydes and esters (overoxidation), and with allylic alcohols because of competing migration of the double bond. Recently, chloroarenes [12] have been described as cooxidants but the procedure requires special ligands.…”
Section: Introductionmentioning
confidence: 99%